Environmental Health: Knowledge and Practice of Perinatal Health Professionals in Southern France. (13th November 2019) - Sunyach, C; Antonelli, B; Tardieu, S; Marcot, M; Perrin, J; Bretelle, F
Abstract: Background: The exposure of adults of reproductive age as well as of pregnant women and children to environmental contaminants is of particular concern, as it can impact fertility, in utero development, pregnancy outcomes and child health. Although worrying, this knowledge provides an opportunity to enforce interventions during these critical reproductive/developmental times, when they may have the greatest effect. Consequently, the World Health Organization (WHO) and international societies advocate including Environmental Health (EH) in perinatal care. Objectives: Our aim was to paint a picture of the current attitudes, representation, knowledge, and training expectations among Perinatal Health Professionals in south-eastern France. Results: In 2017, a cross-sectional study was performed in a large panel of perinatal HPs. Quantitative and qualitative information was collected via auto-questionnaire. Questionnaires were completed by 962 participants, mainly midwives (41.1%), physicians (25.6%) and nursery nurses (11%). Indoor/outdoor air quality and endocrine disruptors were the best-mastered topics, whereas electromagnetic fields and diet gave rise to unsure responses. Overall, perinatal HPs were ill-trained and -informed about the reproductive risks linked to daily environmental exposure. HPs reported scarce knowledge, fear of patient reaction and lack of solutions as the main barriers to providing information regarding EH to the public. Conclusions: In South-eastern France perinatal Health Professionals are eager to incorporate EH in their current practice. Our findings highlight the need to set up EH training programs focused on scientific knowledge and to provide simple messages and tips to help perinatal HPs deliver advice to populations to mitigate exposure to environmental toxicants. Key messages: In South-eastern France perinatal Health Professionals are eager to incorporate EH in their current practice but ask for training. We are currently providing training programs combining practical sessions as well as basic and advanced scientific training adapted to the demand of medical and non-medical professional groups.